Does Monetary Policy Induce Economic Growth? An Empirical Evaluation of the Nigerian Economy - Anthony Ilegbinosa Imoisi (Faculty of Economics, Universitas Sriwijaya, 2018)
Monetary and Fiscal policies are instruments which the government of any nation can employ to effectively achieve the desired growth of their respective economies. This study investigates the extent to which monetary policies can promote economic growth in Nigeria from 1980-2017. Secondary data were used from the Statistical Bulletin of the apex bank in Nigeria (CBN) and National Bureau of Statistics. Unit root test, Johansen co-integration and the vector error correction model (VECM) were employed in analyzing the data collected for this study. The result showed that approximately 62% of GDP is explained by variables in the model while 38% is accounted for and explained by other variables not included in the model but are captured by the error term. In addition, monetary policies did not have a significant impact on Nigeria’s economic growth in the short run, but significantly affected the country’s growth in the long run.